Atroposelective Phosphoric Acid Catalyzed Three‐Component Cascade Reaction: Enantioselective Synthesis of Axially Chiral N‐Arylindoles. (20th September 2019) - Wang, Lei; Zhong, Jialing; Lin, Xufeng
Abstract: An efficient organocatalytic atroposelective three‐component cascade reaction of 2, 3‐diketoesters, aromatic amines, and 1, 3‐cyclohexanediones has been developed for the highly enantioselective synthesis of axially chiral N‐arylindoles. The success of this method derives from the use of a newly developed second‐generation chiral spirocyclic phosphoric acid as the catalyst. In addition, this protocol was extended to the synthesis of an axially chiral monophosphorus ligand. Abstract : Auf Achse : Die erste organokatalytische atropselektive Dreikomponenten‐Heteroanellierung von 2, 3‐Diketoestern, aromatischen Aminen und 1, 3‐Cyclohexandionen wurde entwickelt. Ein breites Spektrum an axial‐chiralen N ‐Arylindolen wurde unter Verwendung eines spirocyclischen Phosphorsäurekatalysators mit hohen Ausbeuten und Enantioselektivitäten gewonnen.